Social support and very young adolescent girl's knowledge on sexual relationships: A comparative qualitative study of Girl Only Clubs' participants and non-participants in rural Malawi. - Wanangwa Chimwaza-Manda; Mphatso Kamndaya; Nanlesta Pilgrim; Sanyukta Mathur; Effie Kondwani Chipeta; Yandisa Sikweyiya (Public Library of Science (PLoS), 2023)
Early sexual relationships are associated with an increased risk of acquiring sexually transmitted diseases including HIV/AIDs, teenage pregnancies, and unsafe abortions among other negative health outcomes. Understanding sexual relationships among very young adolescents (VYAs) is important to equip them to protect themselves from negative sexual health (SH) outcomes. DREAMS (Determined, Resilient, Empowered, AIDS-free, Mentored, and Safe) is an HIV prevention initiative that provided an evidence-based core package of interventions to VYAs to prevent HIV acquisition in 15 countries in sub-Saharan Africa. The Girl Only Club (GOC) was the primary context for the interventions. Our objective in this study was to explore if there was any difference in social support (SS) received concerning sexual relationships between the VYA girls who attended GOCs and those who did not. In-depth interviews were conducted with 43 VYA girls, aged 10-14 years, in two rural southern districts, Zomba and Machinga, in Malawi. Twenty-three VYA girls were participants in GOCs and 20 VYA girls did not participate. A thematic, descriptive approach that involved a constant comparative analysis guided the data analysis, and Nvivo 12 software was used. In both study sites available SS concerning sexual relationships is informational support including information from parents, older relatives, and friends. However, club participants differed from non-club participants in sexual and reproductive health (SRH) knowledge and use. Club participants reported consulting others on decision-making and information on sexual relationships; receiving detailed SH information from clubs; condom use due to education received from the clubs; quitting sexual relationships; and correcting misinformation with club information. GOC participants received more SS which made them more knowledgeable and better at handling sexual relationship issues than those not in clubs. Interventions that integrate SS including social asset building and safe spaces are critical for VYA SRH programming.